Genetic diversity of Herpetospermum caudigerum (Ser.) Baill using AFLP and chloroplast microsatellites. Issue 1 (1st January 2019) - Xu, Fuling; Lei, Pei; Jiang, Mingquan; Sang, Liqun; Guan, Fachun; Meng, Fanjuan; Quan, Hong
Abstract: Herpetospermum caudigerum (Ser.) Baillis is an endangered species found in high altitude regions of Tibet in China. In this work, its genetic diversity and genetic structure were investigated based on nuclear and chloroplast DNA. A total of 426 fragments were scored using 10 amplified fragment length polymorphism (AFLP) primer combinations, and from these, 256 fragments (60.7%) were polymorphic and could differentiate these populations. The dendrogram revealed that populations from different altitude have rich genetic diversities ( Ht = 0.156, Hs = 0.111, G st = 0.287 and Nm = 1.618). The averages of the number of alleles ( Na ), effective number of alleles ( Ne ), Nei's genetic diversity ( H ) and Shannon's index ( I ) were 1.352, 1.188, 0.111 and 0.168, respectively. In addition, 5 P03- trn L- trn F-300 haplotypes and 3 P02- trn L- trn F-396 haplotypes were identified among the 4 populations, and 7 haplotypes were identified based on the combined fragments. The non-coding region P03- trn L- trn F-300 exhibited higher polymorphisms with the number of haplotypes, the abundant haplotype (gene) diversity and the nucleotide diversity. Tajima's test showed that all Tajima's D values were statistically significant at P < 0.05, indicating that natural selection has an effect on mutations in these fragments. Our results from H. caudigerum cpDNA indicated a high genetic diversity fixation index ( Fst = 0.968) and showed greater genetic differentiation among populations (96.7%, P < 0.01) than analysis of nDNA (63.72%, P < 0.01). These results could lay the foundation for further understanding and conservation of H. caudigerum germplasm resources.